Improvement of elements of zonal agro-technology of sweet pepper cultivation on seeds under irrigation conditions of Astrakhan region - A. V. Gulin; M. V. Mukanov; A. S. Karakadzhiev (Овощи России, 2024)
Relevance. The purpose of the research was to improve the elements of zonal agricultural technology for cultivating a new variety of sweet pepper Zarnitsa, to study the possibility of increasing productivity, reducing production costs during its seed production through the use of a non-seedling method of cultivation in irrigated conditions and the plant growth regulator Zircon, R.Methodology. Experimental studies were carried out on the experimental field of All-Russian Research Institute of Irrigated Vegetable and Melon Growing (Astrakhan region) in 2022-2023. The establishment of the field experiment and the carrying out of records and observations in the experiment were carried out in accordance with generally accepted methods.Results. It was found that with the seedless method of growing sweet pepper, the period from sowing to the start of fruit harvesting was 12 days shorter. Sweet pepper plants in the seedling method during the fruiting phase had advantages: in plant height by 9.3%, in the number of lateral shoots by 21.2%, in leaf weight by 7.0%, in average fruit weight by 6.1%. The highest yield, on average 31.6 t/ha, was obtained using the seedling method; when sowing seeds in the ground, it was 3.8% lower. Replacing the seedling method of cultivation with a non-seedling method contributed to a reduction in production costs by 74.7 thousand rub./ha, production costs by 1.9 thousand rub./t, production profitability by 1.2 times, due to savings in labor resources and working capital for growing and planting seedlings. Replacing the seedling method of cultivation with a non-seedling method helped reduce production costs by 74.7 thousand rub./ha, production costs by 1.9 thousand rubles/t, the profitability of production of sweet pepper products and seeds by 1.2 times, due to savings labor resources, working capital for growing, planting seedlings. A single treatment with the plant growth regulator Zircon, P (30 ml/ha) at the beginning of flowering contributed to a significant increase in plant biometric parameters: height by 12.2%, number of lateral shoots by 30.8%, leaf weight by 14.3%, yield by 2.4 t/ha (7.9%), compared to the control (30.4 t/ha), an increase in sugar content by 0.2%, vitamin C by 4 mg% and seed yield by 9 kg/ha (8.7%). The sowing qualities of sweet pepper seeds in all variants of the experiment met the standard requirements and were – 94-95% in terms of germination and – 92-94% in terms of germination energy. The highest level of profitability of 204.9% was obtained as a result of using a growth regulator; in the option without treatment it was lower by 14.4%.